Instructional Support and Professional Development on Competencies of Technology and Livelihood Education Teachers - Windy Sandoval Dioquino; Dr. Aprell Abellana (Researchparks Publishing, 2022)
This study explored the relationship of instructional support and professional development the competencies of Technology and Livelihood Education (TLE) teachers, taking the views and perceptions of some 205 Technology and Livelihood Education (TLE) public school teachers in Region X – Northern Mindanao. This took place in the first quarter of school year 2021-2022. A questionnaire on instructional support, professional development, and teacher competencies were used to obtain the answers to the problems of the study. A descriptive-correlational analysis method of research was utilized. The data gathered were analyzed using frequency counts, percentages, means, and correlation analysis. Through regression, the study determined the predictor variables of Technology and Livelihood Education (TLE) teachers’ competencies in Region X – Northern Mindanao. Instructional materials were found to be seldom provided by schools as these were fairly utilized for use by Technology and Livelihood Education (TLE) teachers. On the other hand, the results for instructional methods revealed that planning strategies, instructional strategies, assessment practices, and curriculum development were highly implemented. The teachers were equipped with the necessary preparations in their function as frontliners in delivering services to their clientele. The professional development of Technology and Livelihood Education (TLE) teachers were found to be satisfactory. This means that schools have seldomly provided teachers with opportunities to attend seminars, workshops, and training. Instructional materials, instructional methods in terms of planning strategies and instructional strategies, and professional development were significantly correlated to the competencies of Technology and Livelihood Education (TLE) teachers. The research and extension activities, seminar/workshop/training, and instructional strategies were the predictors of the Technology and Livelihood Education (TLE) teachers’ competencies.